Effect of adding different levels of red ginseng roots powder to feed on some physiological characteristics of Japanese quail (Coturnix japonica). - Abdul Karim Mazid Al-Waeli; Khalid Chillab Kridie Al-Salhie (University of Thi-Qar Journal of agricultural research, 2020)
The present study was conducted at in the Quail field of the Faculty of the Agriculture/University of Basrah for the period from 21/9/2017 to 12/11/2017 to determine the effect of adding different levels of red ginseng roots powder to feed on some physiological of the Japanese quail. A total of 240 Japanese quail birds aged one week were used in this study. The birds were randomly distributed into four treatments (60 birds for each). Each treatment was replicated three times (20 birds for each). (T1) fed a basal diet without feed additive (control), (T2), (T3), and (T4) were fed a basal diet with adding red ginseng roots powder 250, 500 and750 mg/kg respectively. The results indicated add the red ginseng roots powder has no significant differences between treatments on some blood characteristics (RBCs, PCV and Hb) at 60 days of age in both male and female, while the T4 and T3 treatments were recorded highest value in WBCs and the lowest Value in (H / L) for both male and female compared with the T2 and T1. In conclusion, the red ginseng roots powder has a positive effect to improve the immune status of quails and reduce stress.